The Role of Revenue Recycling Schemes In Environmental Tax Selection : A General Equilibrium Analysis - Timilsina, Govinda R. (The World Bank, 2007)
This study examines the roles of revenue recycling schemes for the selection of alternative tax instruments (i.e., carbon-, sulphur-, energy- and output-tax) to reduce CO2 emissions to a specified level in Thailand. A static, single period, multi-sectoral computable general equilibrium (CGE) model of the Thai economy has been developed for this purpose. This study finds that the selection of a tax instrument to reduce CO2 emissions would be significantly influenced by the scheme to recycle the tax revenue to the economy. If the tax revenue is recycled to finance cuts in the existing labour or indirect tax rates, carbon tax would be more efficient than the sulphur-, energy- and output-taxes to reduce CO2 emissions. On the other hand, if the tax revenue is recycled to households through a lump-sum transfer, sulphur and carbon taxes would be more efficient than energy and output taxes. The ranking between the sulphur and carbon taxes under the lump sum transfer scheme depends on substitution possibility of fossil fuels. Sulphur tax is found superior over carbon tax at the higher substitution possibility between fossil fuels; the reverse is found true at the lower substitution possibility. In all schemes of revenue recycling considered, the output tax is found to be the most costly (i.e., in welfare terms) despite the fact that it generates two to three times higher revenue than the other tax instruments